RNA-Binding Proteins in Amyotrophic Lateral Sclerosis and Neurodegeneration - Ugras, Scott E. (Hindawi Publishing Corporation, 2012)
Amyotrophic Lateral Sclerosis (ALS) is an adult onset neurodegenerative disease, which is universally fatal. While the causes of this devastating disease are poorly understood, recent advances have implicated RNA-binding proteins (RBPs) that contain predicted prion domains as a major culprit. Specifically, mutations in the RBPs TDP-43 and FUS can cause ALS. Cytoplasmic mislocalization and inclusion formation are common pathological features of TDP-43 and FUS proteinopathies. Though these RBPs share striking pathological and structural similarities, considerable evidence suggests that the ALS-linked mutations in TDP-43 and FUS can cause disease by disparate mechanisms. In a recent study, Couthouis et al. screened for protein candidates that were also involved in RNA processing, contained a predicted prion domain, shared other phenotypic similarities with TDP-43 and FUS, and identified TAF15 as a putative ALS gene. Subsequent sequencing of ALS patients successfully identified ALS-linked mutations in TAF15 that were largely absent in control populations. This study underscores the important role that perturbations in RNA metabolism might play in neurodegeneration, and it raises the possibility that future studies will identify other RBPs with critical roles in neurodegenerative disease.